MENINGKATKAN KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN MENEMPEL DENGAN BAHAN ALAM DI TK ABA 001 KECAMATAN KUOK KABUPATEN KAMPAR - Yuneli, Yuneli; Isjoni, Isjoni; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase fine motor skills in children aged 5-6 years through sticking with natural materials in TK ABA 001 Kuok District of Kampar regency. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically n are 5-6 years old children who totaled 15 children in kindergarten ABA 001. Data were obtained through observation and data analysis was done by using quantitative descriptive analysis. Ha sil research shows that the activity of sticking with natural ingredients can improve fine motor skills in children aged 5-6 years. It can be seen from the increase in the average percentage of fine motor skills in the first cycle of 58.0% which is the criteria began to develop according to expectations (BSH) and increased by 40.7% in the second cycle to be 81.6%, which located on the criteria developed very well (BSB). So, sticking with the activity of natural ingredients can improve fine motor skills 5-6 years old children in kindergarten ABA 001 Kuok District of Kampar regency.Keywords : Fine Motor Skill, Activity Sticking with Natural Ingredients